Research on the Dimensional Framework of Digital Marketing Content on Social Media: Coarse Grained and Fine Grained - Yang Liu; Jiaying Wang; Zhijie Zhao (IEEE Access, 2025)
As renowned marketing expert Seth Golding stated that the focus of marketing is no longer on the stuff you make, but on the story content you tell. Existing dimensional analyses of digital marketing content on social media are not agreed upon, and lack a universal content categories. Addressing the gap, the study coordinates Uses and Gratifications Theory and Consumer Perceived Value Theory to design a universal dimensional framework for digital marketing content, presented in both coarse-grained and fine-grained forms. For the Sina Weibo platform, the rationality of the constructed digital marketing content dimension framework is empirically validated by using a approach combining quantitative natural language processing and qualitative content analysis. Results indicate that the dimension framework derived from the two theories effectively identifies the motivations and values expressed in the digital marketing content across both granularity levels. The study expands insights into social media digital marketing content and provides meaningful practical guidance for brands.